In vitro cytotoxicity and docking study of novel symmetric and asymmetric dihydropyridines and pyridines as EGFR tyrosine kinase inhibitors. (2nd May 2022) - Mansour, Basem; Bayoumi, Waleed A.; El‐Sayed, Magda A.; Abouzeid, Laila A.; Massoud, Mohammed A. M.
Abstract: Quinolines have a weighty effect as anticancer agents and 1, 4‐DHPs have demonstrated efficacy as anticancer agents in several studies, as well. New hybrid models of symmetric and asymmetric 1, 4‐DHPs and pyridines linked at C3 of 2‐chloroquinoline as a new anticancer scaffold, were designed and synthesized. Hantszch 1, 4‐DHPs method was adopted for chemical synthesis. MTT assay was performed for the evaluation of cytotoxicity, and EGFR tyrosine kinase assay was performed to investigate binding to our selected compounds, measured by ELISA. The IC50 expressed in µM values revealed that compounds 4a, b, and 5i, k showed the best results against the tested four cell lines than the reference drug 5‐Flurouuracil. Compound 5k displayed the most potent cytotoxic activity with IC50  values in the low µM range (12.03 ± 1.51: 20.09 ± 2.16 µM), compared with 5‐Fu IC50 range (40.74 ± 2.46: 63.81 ± 2.69 µM). The incorporation of 2‐chloroquinoline at C3 to C4 of 1, 4‐DHP could be proposed as an anticancer scaffold rather than its analogous pyridines. Ester fragments connected to 1, 4‐DHPs ring as a lipophilic part are essential for anticancer activity. The chirality at C4 improved the anticancer activity. The hydrogen and halogen bond facilitated protein‐ligand binding mode and affinity. Abstract : Quinolines and DHPs have weighty effect as antitumor agents. New hybrid scaffolds were designed, synthesized and investigated as antitumors. Incorporation of 2‐chloroquinoline at C3 to C4 of 1, 4‐DHP could be proposed as anticancer scaffold rather than its analogous pyridines. The chirality at C4 of DHPs improved the anticancer activity. Compound 5k displayed the most potent cytotoxic activity with IC50 values in the low µM range (12.03 ± 1.51: 20.09 ± 2.16 µM), compared with 5‐Fu IC50 range (40.74 ± 2.46: 63.81 ± 2.69 µM). New inhibitors for EGFR‐TK was discovered.